Adsorption and migration of single metal atoms on the calcite (10.4) surface. (15th February 2017) - Pinto, H; Haapasilta, V; Lokhandwala, M; Öberg, S; Foster, Adam S
Abstract: Transition metal atoms are one of the key ingredients in the formation of functional 2D metal organic coordination networks. Additionally, the co-deposition of metal atoms can play an important role in anchoring the molecular structures to the surface at room temperature. To gain control of such processes requires the understanding of adsorption and diffusion properties of the different transition metals on the target surface. Here, we used density functional theory to investigate the adsorption of 3 d (Ti, Cr, Fe, Ni, Cu), 4 d (Zr, Nb, Mo, Pd, Ag) and 5 d (Hf, W, Ir, Pt, Au) transition metal adatoms on the insulating calcite (10.4) surface. We identified the most stable adsorption sites and calculated binding energies and corresponding ground state structures. We find that the preferential adsorption sites are the Ca–Ca bridge sites. Apart from the Cr, Mo, Cu, Ag and Au all the studied metals bind strongly to the calcite surface. The calculated migration barriers for the representative Ag and Fe atoms indicates that the metal adatoms are mobile on the calcite surface at room temperature. Bader analysis suggests that there is no significant charge transfer between the metal adatoms and the calcite surface.